Glass ceramic solid electrolyte and lithium ion battery
By using glass ceramic solid electrolytes containing lithium, phosphorus, sulfur and halogen in lithium-ion batteries, the problems of low filling rate and insufficient ionic conductivity in the prior art are solved, and efficient battery performance and safety improvements are achieved.
Patent Information
- Application Number
- CN202380050929.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The solid electrolyte filling rate in existing lithium-ion batteries is low and the ionic conductivity is insufficient, making it difficult to meet the requirements of high energy density and safety.
A glass ceramic solid electrolyte containing lithium, phosphorus, sulfur and halogen as constituent elements is used to improve the filling rate and ionic conductivity by adjusting the molar ratio and the conditions of the powder X-ray diffraction peak.
It achieves high filling rate and high ion conductivity, improving the performance and safety of lithium-ion batteries.
Smart Images

Figure BDA0005217897910000181 
Figure HDA0005217897940000011 
Figure HDA0005217897940000012
Abstract
Description
Technical Field
[0001] The invention relates to a glass ceramic solid electrolyte and a lithium ion battery. Background Art
[0002] In recent years, with the rapid popularization of information-related devices and communication devices such as personal computers, video cameras and mobile phones, the development of batteries used as their power sources has also attracted attention. Among these batteries, lithium-ion batteries have attracted attention from the viewpoint of high energy density.
[0003] Since currently commercially available lithium-ion batteries use electrolytes containing flammable organic solvents, it is necessary to install a safety device to suppress the temperature rise during a short circuit, or to improve the structure or materials used to prevent short circuits. In contrast, lithium-ion batteries that are fully solid by changing the electrolyte to a solid electrolyte do not use flammable organic solvents in the battery, so it is believed that safety devices can be simplified and the manufacturing cost and productivity are excellent.
[0004] As a solid electrolyte used for lithium ion batteries, a sulfide solid electrolyte is known (for example, refer to Patent Document 1).
[0005] In order to improve the performance of lithium-ion batteries, it is important to increase the filling rate (compactness) of solid electrolyte powder. In order to increase the filling rate, it is effective to mechanically make the solid electrolyte soft (easy to compress and deform).
[0006] Among lithium ion conductive sulfide solid electrolytes, Li3PS4 glass is known to have a high filling rate. However, the ion conductivity of Li3PS4 glass is low, less than 1 mS / cm.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application No. 2019-506699 Summary of the invention
[0010] The object of the present invention is to provide a glass ceramic solid electrolyte with high filling rate and high ion conductivity.
[0011] According to the present invention, the following glass ceramic solid electrolyte and the like are provided.
[0012] 1. A glass ceramic solid electrolyte comprising lithium, phosphorus, sulfur and halogen as constituent elements,
[0013] The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is 2.0 to 5.3,
[0014] The molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is 2.0 to 4.5,
[0015] The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.1 to 2.3,
[0016] In powder X-ray diffraction using CuKα radiation, a peak A is present at a position of 2θ=20±1°, and in the powder X-ray diffraction, a peak B is not present at a position of 2θ=23.6±1°, or when the peak B is present, the peak intensity (I B ) and the peak intensity of peak A (I A ) peak intensity ratio (I B / I A ) is less than 0.050,
[0017] The crystallite size of the glass ceramic solid electrolyte is 5 to 20 nm.
[0018] 2. The glass ceramic solid electrolyte as described in 1, the peak intensity ratio (I B / I A ) is 0.
[0019] 3. The glass ceramic solid electrolyte according to 1 or 2, which shows a peak derived from lithium halide in powder X-ray diffraction using CuKα rays.
[0020] 4. The glass ceramic solid electrolyte according to 3, wherein the crystallite size of the lithium halide calculated from the peak with the highest intensity among the peaks derived from the lithium halide is 5 to 100 nm.
[0021] 5. The glass ceramic solid electrolyte according to any one of 1 to 4, wherein the relative density of the 400 MPa powder compact is 90% or more.
[0022] 6. A glass ceramic solid electrolyte as described in any one of 1 to 5, wherein the true density is 2.0 to 3.0 g / cm 3 .
[0023] 7. The glass ceramic solid electrolyte according to any one of 1 to 6, wherein the molar ratio (X / P) is greater than 0.86.
[0024] 8. The glass ceramic solid electrolyte according to any one of 1 to 7, comprising two or more of the halogens.
[0025] 9. The glass ceramic solid electrolyte as described in 8, wherein the halogen includes iodine and bromine.
[0026] 10. The glass ceramic solid electrolyte according to 9, wherein the molar ratio (I / P) of the iodine (I) to the phosphorus (P) is 0.0<(I / P)<1.8,
[0027] The molar ratio (Br / P) of the bromine (Br) to the phosphorus (P) is 0.0<(Br / P)<1.5.
[0028] 11. The glass ceramic solid electrolyte according to any one of 1 to 10, wherein the ion conductivity is 1 mS / cm or more.
[0029] 12. A lithium ion battery comprising the glass ceramic solid electrolyte as described in any one of 1 to 11.
[0030] According to the present invention, a glass ceramic solid electrolyte having a high filling rate and high ion conductivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram for explaining a particle density measuring device.
[0032] Figure 2 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 1 to 4.
[0033] Figure 3 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 5 to 8.
[0034] Figure 4 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 9 to 12.
[0035] Figure 5 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 13 to 16.
[0036] Figure 6 These are the X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 17 to 21.
[0037] Figure 7 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Comparative Examples 1 to 5.
[0038] Figure 8 These are X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Comparative Examples 6 to 11. DETAILED DESCRIPTION
[0039] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limits of the numerical ranges of "above", "below", and "to" are numerical values that can be combined arbitrarily, and the numerical values of the embodiments can also be used as the upper and lower limits.
[0040] The glass ceramic solid electrolyte according to one embodiment of the present invention contains lithium, phosphorus, sulfur and halogen as constituent elements, and the molar ratio of the above constituent elements to phosphorus ((Li, S, X) / P) satisfies the following range.
[0041] Li / P=2.0~5.3
[0042] S / P=2.0~4.5
[0043] X / P=0.1~2.3
[0044] Furthermore, the glass ceramic solid electrolyte of the present embodiment satisfies the following conditions A to C.
[0045] A. In powder X-ray diffraction using CuKα rays, a peak A exists at the position of 2θ=20±1°.
[0046] B. In the powder X-ray diffraction, there is no peak B at the position of 2θ=23.6±1°, or when there is peak B, the peak intensity (I B ) and the peak intensity of peak A (I A ) peak intensity ratio (I B / I A ) is less than 0.05.
[0047] C. The crystallite size of the glass ceramic solid electrolyte calculated from peak A using the Scherrer formula is 5 to 20 nm.
[0048] The glass ceramic solid electrolyte according to the embodiment of the present invention satisfies the above-mentioned conditions of composition and diffraction peak, and has a high filling rate which is equal to or higher than that of conventional glass solid electrolytes, and also has high ion conductivity.
[0049] In addition, in the present application, a glass ceramic solid electrolyte refers to a solid electrolyte in which a peak originating from a solid electrolyte is observed in an X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement, and is a material that is independent of whether or not there is a peak originating from a raw material of the solid electrolyte. That is, the glass ceramic solid electrolyte includes a crystalline structure originating from a solid electrolyte, and may be a part of the crystalline structure originating from the solid electrolyte, or may be a whole crystalline structure originating from the solid electrolyte. Furthermore, if the glass ceramic solid electrolyte has an X-ray diffraction pattern as described above, an amorphous component (also referred to as a "glass component") may also be included in a part thereof. In addition, in a crystalline solid electrolyte, a so-called glass ceramic obtained by heating an amorphous solid electrolyte (glass component) to a temperature above the crystallization temperature is included.
[0050] In the glass ceramic solid electrolyte of the present embodiment, the molar ratio (Li / P) of lithium (Li) to phosphorus (P) is preferably 3.0 to 5.25, and more preferably 3.5 to 5.20. The molar ratio (S / P) of sulfur (S) to phosphorus (P) is preferably 3.0 to 4.4, and more preferably 3.5 to 4.3. The molar ratio (X / P) of halogen (X) to phosphorus (P) is preferably greater than 0.75, and more preferably greater than 0.86.
[0051] In the glass ceramic solid electrolyte of the present embodiment, the halogen (X) preferably includes one or more selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and more preferably includes Br or I. In addition, the halogen (X) preferably includes bromine (Br) and iodine (I).
[0052] Preferably, the molar ratio (I / P) of iodine (I) to phosphorus (P) is 0.0 to 1.8, and the molar ratio (Br / P) of bromine (Br) to phosphorus (P) is 0.0 to 1.5.
[0053] The types and molar ratios of the constituent elements of the glass ceramic solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.
[0054] The molar ratio of the constituent elements of the glass ceramic solid electrolyte can be adjusted by controlling the raw material blending. In addition, the molar ratio of the constituent elements in the raw materials is substantially equal to the molar ratio of the constituent elements of the obtained glass ceramic solid electrolyte.
[0055] In the glass ceramic solid electrolyte of the present embodiment, the molar ratio (Li / P) of lithium (Li) to phosphorus (P) and the molar ratio (X / P) of halogen (X) to phosphorus (P) preferably satisfy the following relational expression (1).
[0056] Li / P=3±α+X / P (1)
[0057] (In the formula, α is 0 to 0.5.)
[0058] By satisfying formula (1), PS4 as the main skeleton of the glass ceramic solid electrolyte 3- The amount of tetrahedral structure generated increases, which has the effect of reducing the amount of hydrogen sulfide generated in low dew point environments. 3- The larger and more rigid P2S6 4- Structure or P2S7 4- Since the amount of structure generated is reduced, the softness of the glass ceramic solid electrolyte can be improved.
[0059] The value α in the formula (1) may be 0 to 0.3, 0 to 0.1, or even 0.
[0060] In the powder X-ray diffraction measurement using CuKα rays, the glass ceramic solid electrolyte of the present embodiment has a peak A at 2θ=20±1°, and the crystallite size of the glass ceramic solid electrolyte calculated from the peak A is 1 to 20 nm. The crystallite size of the glass ceramic solid electrolyte calculated from the peak A is preferably 2 to 18 nm. Since the crystallite size is small, when the glass ceramic solid electrolyte is compressed, it can be compressed in a manner that the crystallites are not damaged. In addition, since the crystallite size is not too small, the ionic conductivity of the glass ceramic solid electrolyte can also be maintained at a high level. As a result, the glass ceramic solid electrolyte of the present embodiment can take into account both high filling rate and high ionic conductivity.
[0061] Generally, the diffraction peak measured by powder X-ray diffraction has a width, and the width of the peak at half the height of the peak after removing the background is called the half width. It is known that the half width is correlated with the crystallite size. The larger the crystallite size, the higher the crystallinity and the higher the repetitive regularity of the crystal structure, so the intensity of the diffraction peak measured by powder X-ray diffraction becomes stronger and the half width becomes narrower.
[0062] The details of the measurement method are shown in Examples.
[0063] In addition, in the powder X-ray diffraction measurement, there is no peak B at the position of 2θ=23.6±1°, or in the case where there is peak B, the peak intensity (I B ) and the peak intensity of peak A (I A ) peak intensity ratio (I B / I A ) is less than 0.05.
[0064] The peaks A and B are Li 4-x Ge 1-x P xS4 is a diffraction peak of a thio-LISICONRegion II type crystal structure or a crystal structure similar to the thio-LISICONRegion II type crystal structure.
[0065] In the glass ceramic solid electrolyte of the present embodiment, it is characterized in that the peak A is observed with high intensity, but the peak B is not observed or its intensity is extremely low. The present embodiment found that the filling rate of the glass ceramic solid electrolyte having such peaks is higher than or equal to that of the conventional glass ceramic solid electrolyte and has high ionic conductivity.
[0066] Peak intensity ratio I B / I A Preferably 0.
[0067] In one embodiment, the glass ceramic solid electrolyte shows a diffraction peak derived from a lithium halide in a powder X-ray diffraction measurement using CuKα rays. The crystallinity of the lithium halide observed in the powder X-ray diffraction measurement of the glass ceramic solid electrolyte is lower than that of the lithium halide as a raw material. It can be considered that, since the lithium halide itself is a soft material, even if there is a degree of crystallinity that can detect the peak of the lithium halide in the powder X-ray diffraction measurement, there is almost no curing effect on the glass ceramic solid electrolyte of the present embodiment.
[0068] In the glass ceramic solid electrolyte of the present embodiment, the crystallite size calculated from the peak half width of the peak with the largest intensity among the diffraction peaks derived from lithium halide is preferably 5 to 100 nm, more preferably 10 to 90 nm.
[0069] The crystallite size can be adjusted by composition or crystallization temperature. For example, the crystallite size can be adjusted by adjusting the molar ratio (Li / P) of lithium (Li) to phosphorus (P), the molar ratio (Br / X) of bromine (Br) to halogen (X), and the molar ratio (I / P) of iodine (I) to phosphorus (P). In addition, by increasing the crystallization temperature, the crystallite size becomes larger, so the crystallite size can also be adjusted by the crystallization temperature.
[0070] The peak half width is calculated from the XRD pattern. Details of the measurement and calculation methods are described in the Examples.
[0071] The calculation object of the peak half width is, for example, the intensity of the diffraction peak of 2θ=45.0±1° when the lithium halide is LiF; the intensity of the diffraction peak of 2θ=30.1±1° when the lithium halide is LiCl; the intensity of the diffraction peak of 2θ=28±1° when the lithium halide is LiBr; and the intensity of the diffraction peak of 2θ=25.5±1° when the lithium halide is LiI.
[0072] In addition, the peak half width is calculated based on the peak of the lithium halide with the largest amount of halogen added as a raw material when manufacturing the glass ceramic solid electrolyte. When the amounts of the two lithium halides are equal in molar ratio, the peak of the lithium halide with the largest peak intensity is calculated.
[0073] In one embodiment, the true density (g / cm 3 ) is preferably 2.0 to 3.0 g / cm 3 The true density in the above range means that PS4, the main skeleton of the glass ceramic solid electrolyte, 3- The structure and the total halogen content fall within a certain range, and the glass-ceramic solid electrolyte of this embodiment can have both high conductivity and high softness.
[0074] The true density of the glass ceramic solid electrolyte of the present embodiment is more preferably 2.01 to 2.9 g / cm 3 , particularly preferably 2.02 to 2.8 g / cm 3 .
[0075] The true density of the glass ceramic solid electrolyte can be measured, for example, by a gas phase replacement method using helium (He) gas. The method for measuring the true density of the glass ceramic solid electrolyte is described in the Examples.
[0076] In the glass ceramic solid electrolyte of the present embodiment, the relative density of the glass ceramic solid electrolyte when made into a 400 MPa powder compact is preferably 90% or more. The relative density can also be set to 90.5% or more, or 91% or more. Usually, the relative density of a 400 MPa powder compact is 99% or less.
[0077] In the present application, the relative density of a 400 MPa powder compact refers to the ratio of the density of a glass ceramic solid electrolyte when compressed at 400 MPa (referred to as particle density) to the true density of the glass ceramic solid electrolyte (relative density = particle density / true density). A higher relative density indicates a higher filling rate.
[0078] The details of the method for measuring the relative density of a 400 MPa powder compact are described in the Examples.
[0079] The ion conductivity of the glass ceramic solid electrolyte of the present embodiment can be 1 mS / cm or more, and can also be 1.5 mS / cm or more.
[0080] The method of measuring the ionic conductivity is shown in the Examples.
[0081] The glass ceramic solid electrolyte of the present embodiment can be produced, for example, by mixing and grinding starting materials of a known lithium ion sulfide solid electrolyte so that the molar ratio of the constituent elements satisfies a predetermined range, vitrifying the mixture, and further heat-treating the obtained product to ceramicize the mixture.
[0082] As raw materials for the glass ceramic solid electrolyte of this embodiment, two or more compounds containing lithium, phosphorus, sulfur and halogen as constituent elements can be used; or monomers can be used in combination, and any one can be used without particular restrictions as long as the ionic conductivity caused by the metal atoms contained therein is exhibited.
[0083] Examples of raw materials containing lithium (Li) include lithium compounds such as lithium sulfide (Li2S), lithium oxide (Li2O), and lithium carbonate (Li2CO3), and lithium metal monomers, etc. Among them, lithium compounds are preferred, and lithium sulfide is more preferred.
[0084] The lithium sulfide can be used without particular limitation, but high-purity lithium sulfide is preferred. Lithium sulfide can be produced by the methods described in, for example, Japanese Patent Application Laid-Open Nos. 7-330312, 9-283156, 2010-163356, and 2011-84438.
[0085] Specifically, lithium hydroxide and hydrogen sulfide are reacted at 70° C. to 300° C. in a hydrocarbon organic solvent to generate lithium hydrosulfide, and then the reaction solution is desulfurized to synthesize lithium sulfide (Japanese Patent Application Laid-Open No. 2010-163356).
[0086] Alternatively, lithium sulfide can be synthesized by reacting lithium hydroxide and hydrogen sulfide at 10° C. to 100° C. in an aqueous solvent to generate lithium hydrosulfide, and then desulfurizing and hydrogenating the reaction solution (Japanese Patent Application Laid-Open No. 2011-84438).
[0087] As raw materials containing phosphorus (P), for example, phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), phosphorus compounds such as sodium phosphate (Na3PO4), and phosphorus monomers can be cited. Among them, phosphorus sulfide is preferred, and phosphorus pentasulfide (P2S5) is more preferred. Phosphorus compounds such as phosphorus pentasulfide (P2S5) and phosphorus monomers can be used without particular limitation as long as they are industrially manufactured and sold.
[0088] As the raw material containing halogen (X), for example, it is preferable to contain a halogen compound represented by the following formula.
[0089] M l -X m
[0090] In the formula, M represents sodium (Na), lithium (Li), boron (B), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), germanium (Ge), arsenic (As), selenium (Se), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), or a substance obtained by bonding oxygen or sulfur to these elements, preferably lithium (Li) or phosphorus (P), more preferably lithium (Li).
[0091] X is a halogen element selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).
[0092] In addition, l is an integer of 1 or 2, and m is an integer of 1 to 10. When m is an integer of 2 to 10, that is, when there are a plurality of Xs, Xs may be the same or different. For example, in SiBrCl3 described later, m is 4, and X is composed of different elements such as Br and Cl.
[0093] Specific examples of the halogen compound represented by the above formula include: sodium halides such as NaI, NaF, NaCl, and NaBr; lithium halides such as LiF, LiCl, LiBr, and LiI; boron halides such as BCl3, BBr3, and BI3; aluminum halides such as AlF3, AlBr3, AlI3, and AlCl3; silicon halides such as SiF4, SiCl4, SiCl3, Si2Cl6, SiBr4, SiBrCl3, SiBr2Cl2, and SiI4; phosphorus halides such as PF3, PF5, PCl3, PCl5, POCl3, PBr3, POBr3, PI3, P2Cl4, and P2I4; and SF2, SF4, SF6, and S2F. 10 , SCl2, S2Cl2, S2Br2 and other sulfur halides; GeF4, GeCl4, GeBr4, GeI4, GeF2, GeCl2, GeBr2, GeI2 and other germanium halides; AsF3, AsCl3, AsBr3, AsI3, AsF5 and other arsenic halides; SeF4, SeF6, SeCl2, SeCl4, Se2Br2, SeBr4 and other selenium halides; SnF4, SnCl4, SnBr4, SnI4, SnF2, SnCl2, SnBr2, SnI2 and other tin halides; SbF3, SbCl3, SbBr3, SbI3, SbF5, SbCl5 and other antimony halides; TeF4, Te2F 10 , TeF6, TeCl2, TeCl4, TeBr2, TeBr4, TeI4 and other tellurium halides; PbF4, PbCl4, PbF2, PbCl2, PbBr2, PbI2 and other lead halides; BiF3, BiCl3, BiBr3, BiI3 and other bismuth halides, etc.
[0094] Among them, lithium halides such as lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), and phosphorus halides such as phosphorus pentachloride (PCl5), phosphorus trichloride (PCl3), phosphorus pentabromide (PBr5), and phosphorus tribromide (PBr3) are preferably exemplified. Among them, lithium halides such as LiCl, LiBr, and LiI, and PBr3 are preferred, lithium halides such as LiCl, LiBr, and LiI are more preferred, and LiI and LiBr are more preferred.
[0095] As the halogen compound, one of the above compounds may be used alone, or two or more of them may be used in combination. That is, at least one of the above compounds may be used.
[0096] In this embodiment, the raw material preferably comprises a lithium compound, a phosphorus compound, and one or more halogen compounds, and at least one of the lithium compound and the phosphorus compound contains elemental sulfur. It is more preferably a combination of lithium sulfide, phosphorus sulfide and two or more lithium halides, and further preferably a combination of lithium sulfide, phosphorus pentasulfide and two or more lithium halides.
[0097] For example, as the raw materials of the glass ceramic solid electrolyte of the present invention, when lithium sulfide, phosphorus pentasulfide, and two or more lithium halides are used, the molar ratio of lithium sulfide to phosphorus pentasulfide in the molar ratio of the input raw materials is preferably 65 to 85:15 to 35, more preferably 70 to 80:20 to 30, further preferably 72 to 78:22 to 28, and particularly preferably 75:25.
[0098] In addition, when the amount of Li3PS4 calculated based on the constituent elements Li, P and S of lithium sulfide and phosphorus pentasulfide is set to 100 mol parts, the lithium halide is preferably set to 10 to 250 mol parts, more preferably 50 to 225 mol parts, and can also be set to 70 to 200 mol parts.
[0099] In this embodiment, mechanical stress is applied to the raw materials to make them react, thereby producing an intermediate (glass-like powder). Here, "applying mechanical stress" means mechanically applying shear force or impact force, etc. As a way of applying mechanical stress, for example, a pulverizer or kneader such as a planetary ball mill, a vibration mill, or a rolling mill can be used. The pulverization and mixing are carried out by strong mechanical stress until at least a part of the raw material powder becomes a state in which the crystallinity cannot be maintained.
[0100] As the conditions for pulverizing and mixing, for example, when a planetary ball mill is used as a pulverizer, the rotation speed is set to tens to hundreds of revolutions per minute, and the treatment is performed for 0.5 hours to 100 hours. More specifically, in the case of the planetary ball mill (model P-5 made by FRITSCH) used in the examples of the present application, the rotation speed of the planetary ball mill is preferably 100 rpm to 400 rpm, and more preferably 150 rpm to 300 rpm.
[0101] When using zirconia balls as the grinding medium, for example, the diameter thereof is preferably 0.2 to 20 mm.
[0102] The temperature during pulverization is not particularly specified, but is preferably 200° C. or lower in order to prevent the solid electrolyte itself from crystallizing and solidifying.
[0103] The intermediate prepared by pulverizing and mixing is subjected to a heat treatment. Specifically, the intermediate is heated to a temperature at which a differential thermal and thermogravimetric analysis (TGDTA) is performed on the intermediate at a temperature increase of 10°C / min using a differential thermal and thermogravimetric analysis (TGDTA) apparatus, and the temperature of the peak top of the exothermic peak observed on the lowest temperature side (T c1 ) as a starting point, preferably set to 5°C or less, more preferably set to 10°C or less, and further preferably set to a range of 15°C or less. There is no particular restriction on the lower limit, and it can be set to a temperature of about -10°C or more at the peak top of the exothermic peak observed on the lowest temperature side. By setting it to such a temperature range, the glass ceramic solid electrolyte of this embodiment can be obtained more efficiently.
[0104] The heating temperature for obtaining the glass ceramic solid electrolyte of the present embodiment cannot be uniformly specified, but is generally preferably below 250°C, more preferably below 225°C, and further preferably below 200°C. There is no particular restriction on the lower limit, but it is preferably above 100°C, more preferably above 110°C, and further preferably above 120°C.
[0105] The heating time is not particularly limited as long as it is the time to obtain the desired glass ceramic solid electrolyte, for example, preferably more than 10 minutes, more preferably more than 30 minutes, more preferably more than 60 minutes, and more preferably more than 2 hours. In addition, the upper limit of the heating time is not particularly limited, preferably less than 10 hours, more preferably less than 8 hours, more preferably less than 6 hours, and more preferably less than 4 hours.
[0106] The atmosphere for the heat treatment is not particularly limited, and the heat treatment may be carried out in a hydrogen sulfide gas stream, in an inert gas atmosphere such as nitrogen or argon, or in a vacuum atmosphere.
[0107] The filling rate of the glass ceramic solid electrolyte of the present embodiment is higher than that of the previous glass ceramic solid electrolyte, and has high ionic conductivity, so it can be preferably used in a battery. When lithium is used as a conductive material, it is particularly preferred. The glass ceramic solid electrolyte of the present embodiment can be used for a positive electrode layer, a negative electrode layer, or an electrolyte layer.
[0108] A lithium ion battery according to one embodiment of the present invention includes the above-described glass ceramic solid electrolyte of the present invention. For example, an all-solid lithium ion battery can be manufactured by using the glass ceramic solid electrolyte of the present invention instead of a liquid electrolyte.
[0109] All-solid lithium-ion batteries are mainly composed of a positive electrode layer, a negative electrode layer and an electrolyte layer, and the glass ceramic solid electrolyte of the present invention can be used in any layer. In addition, each layer can be manufactured by a known method.
[0110] For example, when used for a positive electrode layer or a negative electrode layer, a positive electrode active material or a negative electrode active material is mixed and dispersed in the glass ceramic solid electrolyte of the present invention to obtain a positive electrode composite material or a negative electrode composite material.
[0111] As the positive electrode active material, any positive electrode active material can be used without particular limitation as long as it can promote the battery chemical reaction caused by the lithium element, which is preferably used as an element showing ionic conductivity in this embodiment, due to its relationship with the negative electrode active material. As the positive electrode active material that can perform such insertion and extraction of lithium ions, oxide-based positive electrode active materials, sulfide-based positive electrode active materials, etc. can be cited.
[0112] As oxide-based positive electrode active materials, preferred examples include lithium-containing transition metal composite oxides such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel cobalt manganese oxide), NCA (lithium nickel cobalt aluminum oxide), LNCO (lithium nickel cobalt oxide), and olivine-type compounds (LiMeNPO4, Me = Fe, Co, Ni, Mn).
[0113] Examples of the sulfide-based positive electrode active material include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2).
[0114] In addition to the above-mentioned positive electrode active materials, niobium selenide (NbSe 3 ) or the like can also be used.
[0115] In this embodiment, the positive electrode active material can be used alone or in combination of two or more.
[0116] As the negative electrode active material, any negative electrode active material can be used without particular limitation as long as it can promote the battery chemical reaction accompanying the movement of lithium ions, wherein the battery chemical reaction is caused by the element preferably used as the element showing ion conductivity in this embodiment, preferably a metal that can form an alloy with the lithium element, its oxide, an alloy of the metal and the lithium element, etc., preferably lithium element. As the negative electrode active material that can perform such insertion and extraction of lithium ions, any material known as a negative electrode active material in the battery field can be used without limitation.
[0117] Examples of such negative electrode active materials include metallic lithium such as metallic lithium, metallic indium, metallic aluminum, metallic silicon, and metallic tin, or metals capable of forming alloys with metallic lithium, oxides of these metals, or alloys of these metals with metallic lithium.
[0118] The electrode active material used in the present embodiment may have a coating layer on the surface of which is coated.
[0119] As a material for forming the coating layer, an element showing ionic conductivity in the crystalline sulfide solid electrolyte used in this embodiment can be cited, preferably an ion conductor such as a nitride, an oxide, or a composite of lithium. Specifically, lithium nitride (Li3N), a Li4GeO4-based structure such as Li 4-2x Zn x Conductors with a crystalline lithium superion conductor (LISICON) structure such as GeO4, and conductors with a Li3PO4 skeleton structure such as Li 4-x Ge 1-x P x S4 and other conductors with thio-LISICON crystal structures, La 2 / 3-x Li 3x Conductors with a perovskite crystal structure such as TiO3, conductors with a sodium superion conductor (NASICON) crystal structure such as LiTi2(PO4)3, etc.
[0120] In addition, Li y Ti 3-y O4(0<y<3), Li4Ti5O 12 Conductors of metals such as lithium titanate (LTO), LiNbO3, LiTaO3, etc., which belong to the 5th group of the periodic table, or oxide-based conductors such as Li2O-B2O3-P2O5, Li2O-B2O3-ZnO, Li2O-Al2O3-SiO2-P2O5-TiO2, etc.
[0121] The electrode active material having a coating layer can be obtained, for example, by attaching a solution containing various elements constituting a material for forming the coating layer to the surface of the electrode active material and calcining the attached electrode active material preferably at 200° C. to 400° C.
[0122] Here, as the solution containing various elements, for example, a solution containing alkoxides of various metals such as lithium ethoxide, titanium isopropoxide, niobium isopropoxide, tantalum isopropoxide, etc. can be used. In this case, as the solvent, an alcohol solvent such as ethanol and butanol; an aliphatic hydrocarbon solvent such as hexane, heptane, octane; an aromatic hydrocarbon solvent such as benzene, toluene, xylene, etc. can be used.
[0123] In addition, the above-mentioned attachment may be performed by dipping, spraying, or the like.
[0124] From the viewpoint of improving manufacturing efficiency and battery performance, the firing temperature is preferably 200° C. to 400° C., more preferably 250° C. to 390° C., and the firing time is usually about 1 minute to 10 hours, preferably 10 minutes to 4 hours.
[0125] As the coating rate of coating layer, it is preferably more than 90% based on the surface area of electrode active material, more preferably more than 95%, and further preferably 100%, that is, preferably the whole face is coated. In addition, the thickness of coating layer is preferably more than 1nm, more preferably more than 2nm, and is preferably below 30nm as the upper limit, more preferably below 25nm.
[0126] The thickness of the coating layer can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage ratio can be calculated from the thickness of the coating layer, elemental analysis values, and BET specific surface area.
[0127] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a material such as Au, Pt, Al, Ti or Cu that reacts with the above-mentioned glass ceramic solid electrolyte with Au etc. can be used.
[0128] Example
[0129] Hereinafter, the present invention will be described in detail based on examples. The present invention is not limited to the examples. The following is a method for evaluating the samples prepared in each example.
[0130] (1) Powder X-ray diffraction (XRD) measurement
[0131] The powder of the glass solid electrolyte prepared in each example was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and leveled with glass. The filled sample was measured using a kapton film without contact with air using XRD. The 2θ position of the diffraction peak was determined by LeBail analysis using the XRD analysis program RIETAN-FP.
[0132] Powder X-ray diffraction measurement was carried out under the following conditions.
[0133] Device used: BRUKER "D2PHASER"
[0134] Tube voltage: 30kV
[0135] Tube current: 10mA
[0136] X-ray wavelength: Cu-Kα ray
[0137] Optical system: Concentration method
[0138] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (Ni plate)
[0139] Detector: Semiconductor detector
[0140] Measuring range: 2θ=10-60°(deg)
[0141] Step width, scanning speed: 0.05°, 0.05° / sec
[0142] In the analysis of the peak position for confirming the presence of the crystal structure from the measurement results, the peak position was determined by correcting the baseline using an 11th-order Legendre orthogonal polynomial using an XRD analysis program RIETAN-FP.
[0143] (2) Peak half width
[0144] As an example, the calculation method of the peak within the range of 2θ = 20 ± 1° is shown below. In addition, in the peak half width of lithium halide, in the case of LiI, the peak is calculated as 2θ = 25.5 ± 1°, and in the case of LiBr, the peak is calculated as 2θ = 28 ± 1°.
[0145] In the above-mentioned range where the peak exists (2θ=19 to 21°), the half width E is determined so that the difference between the measured value of the intensity (the vertical axis value of the XRD pattern) and the calculated value described below is minimized.
[0146] The ratio of the Lorentzian function is set to A (0≤A≤1), the intensity correction value is set to B, the angle of 2θ at which the intensity becomes maximum is set to C, the angle (2θ) of the calculated intensity is set to D, the half width is set to E, and the background is set to F. In addition, since the background is sometimes affected by amorphous materials, a uniform background O and a linear function P that changes according to the peak position can also be used to calculate F=O+P×D.
[0147] The measured value of the intensity at the angle (2θ) of the calculated intensity is set as G, and the variables are set as A, B, C, E, O, and P. For each angle (2θ) at which the intensity is measured, the deviation H between the measured value and the calculated value of the intensity is calculated by the following formula (2).
[0148] H=G-{B×{A / (1+4×(DC) 2 / E 2 )+(1-A)×exp(-1×(DC) 2 / E 2 )×(4ln(2))}+O+P×D} (2)
[0149] H was summed within the range of 2θ=19 to 21°, and the sum was minimized in a GRG nonlinear manner using the solver function of spreadsheet software Excel (Microsoft), thereby determining the above variables including the half width E.
[0150] (3) Crystallite size
[0151] In order to correct the expansion of the half width caused by the device, the half width E calculated by the above method is corrected using NIST standard Si (640d, crystallite diameter 525nm). If the corrected half width is set to B correction , the corrected half width β used in calculating the crystallite size is expressed by the following formula.
[0152] β=E―B correction
[0153] The actual crystallite size L is calculated by the following formula.
[0154] L = K × λ / (β cos (C / 2))
[0155] Here, the constant K is set to 0.9, and the wavelength of the X-ray used in the measurement is used as λ. In addition, C is the angle (2θ) of the peak center position when calculating the half width.
[0156] (4) Relative density of 400MPa powder compact
[0157] (Measurement of true density)
[0158] The true density is measured by a gas phase replacement method (MicrotracBEL: BELMAX) using helium (He) gas. Calculate the volume inside the sample cell when the pressure of helium (He) gas is set to 55KPa, 60KPa, 65KPa, 70KPa, 75Kpa, 80Kpa, 85KPa, 90Kpa, 95Kpa, 100Kpa, 105Kpa, and 110KPa, and set the average value as the internal volume of the sample cell. In addition, the weight of the sample cell is calculated using an electronic balance. The capacity and weight of the empty (blank) sample cell are measured three times by the above method, and the average value is set as the empty sample cell capacity V1, and the weight is set as the empty sample cell weight W1. Put the glass solid electrolyte into the sample cell, and measure the capacity of the gas phase part of the sample cell and the total weight of the sample cell three times by the above method, and set the average value as the capacity V2 excluding the sample, and the total weight of the sample cell is set as W2.
[0159] The true density d of the glass solid electrolyte can be calculated by the following formula.
[0160] d=(W2-W1) / (V1-V2)
[0161] In addition, regarding the true density of the sample, the average value obtained by performing the above operation and the above formula three times is set as the true density of the sample. The standard deviation of the true density calculated by this method is 0.05 g / cm 3 the following.
[0162] (Measurement of particle density)
[0163] A schematic diagram of the particle density measurement device is shown in Figure 1 shown.
[0164] The sample 10 was filled into a cylindrical jig 11 (manufactured by MACOR (registered trademark)) and pressurized at 400 MPa using a uniaxial press via a stainless steel piston 12. The length L of the device in a state where no sample was filled (blank) was int , and the length L of the device containing the pressurized sample after The height of the sample (particle) is measured by the difference in pellet .
[0165] Specifically, the piston 12 is inserted to a diameter of 10 mm (cross-sectional area S pellet : 0.785cm 2 ) of the cylindrical fixture 11. The cylindrical fixture 11 is rotated 90° in a direction perpendicular to the pressurizing direction, and four measurements are performed, and the average value is set as L int(cm). At this time, the bolt 13 and the nut 14 were tightened at 8 N·m using a torque wrench, and the measurement was performed while the piston 12 was pressurized.
[0166] Next, 0.3 g of the powder of the glass solid electrolyte as a sample is weighed by an electronic balance and put into the cylindrical fixture 11. After being put in, the piston 12 is pressurized by a uniaxial press, thereby pressurizing the sample. The pressure is set to 185 MPa and maintained for 2 minutes, and then the pressure is released. The sample cell is rotated 120° in a direction perpendicular to the pressurization direction and pressurized in the same manner. Then, it is rotated 120° again and pressurized in the same manner. Next, the pressure is set to 400 MPa, and the sample is pressurized in the same manner as in the case of 185 MPa.
[0167] After forming, with L int Repeat the measurement 4 times and set the average value as L. after (cm). Particle density d pellet It is calculated by the following formula.
[0168] d pellet =0.3 / {(L after -L int )×S pellet}
[0169] (Calculation of relative density)
[0170] It is calculated by the following formula.
[0171] Relative density (%) = particle density × 100 / true density
[0172] (5) Ionic conductivity
[0173] The glass ceramic solid electrolyte prepared in each example was formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm, thus making a sample. The top and bottom of the sample were taken as electrode terminals, and measured by the AC impedance method at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is set as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.
[0174] R=ρ(L / S)
[0175] σ=1 / ρ
[0176] (6)ICP measurement
[0177] The powder of the solid electrolyte produced in each example was weighed and collected in a vial under an argon atmosphere. A KOH alkaline aqueous solution was added to the vial, and the sample was dissolved while paying attention to capturing the sulfur component, and appropriately diluted to prepare a measurement solution. It was measured by a Paschen-Runge type ICP-OES device (SPECTROARCOS manufactured by SPECTRO) to determine its composition.
[0178] The standard curve solutions of Li, P, and S were prepared using 1000 mg / L standard solutions for ICP measurement, and the standard curve solutions of Cl and Br were prepared using 1000 mg / L standard solutions for ion chromatography.
[0179] Two measurement solutions were prepared for each sample, and each measurement solution was measured five times to calculate the average value. The composition was determined from the average value of the measurement values of the two measurement solutions.
[0180] Example 1
[0181] [Production of glass ceramic solid electrolyte]
[0182] Lithium sulfide was weighed to 2.319 g, phosphorus pentasulfide to 3.740 g, and lithium iodide to 3.941 g, and 600 g of 10 mm diameter zirconia balls were placed in a 500 mL zirconia can and sealed. Table 1 shows the molar ratio of the starting materials.
[0183] The mixture was pulverized (mechanically ground) using a planetary ball mill (manufactured by Fritsch, Model P-5) at room temperature at a rotation speed of 220 rpm for 40 hours to obtain an intermediate (glass-like powder).
[0184] About 2 g of the intermediate powder was kept at 155° C. for 2 hours under vacuum and then slowly cooled to obtain a glass ceramic solid electrolyte.
[0185] In addition, using a differential thermal and thermogravimetric simultaneous analysis device (TGDTA device), differential thermal and thermogravimetric simultaneous measurement (TGDTA) was performed at a temperature increase condition of 10°C / min, and the peak top temperature (T c1 ) is 170°C.
[0186] The ionic conductivity (σ) of the obtained glass ceramic solid electrolyte is 3.8 mS / cm. Figure 1 Shown is the XRD pattern of the glass-ceramic solid electrolyte.
[0187] Examples 2 to 21, Comparative Examples 1 to 11
[0188] A glass ceramic solid electrolyte was prepared and evaluated in the same manner as in Example 1 except that the raw material composition ratio and the heating temperature of the intermediate were changed as shown in Table 1. The results are shown in Tables 1 and 2.
[0189] In Table 1, the amount of Li3PS4 is set to 100 parts by mole, which corresponds to 150 parts by mole of Li2S and 50 parts by mole of P2S5 as the starting materials.
[0190] In addition, the heating temperature was set to the temperature (T c1 ) is 15°C or less, and in Comparative Example 2, it is set to be equal to T c1 The same temperature is set as T in Comparative Examples 3 and 8. c1 Higher temperatures.
[0191] The molar ratio (X / P) of each element of the glass ceramic solid electrolyte to phosphorus (P) was measured by ICP for Examples 2, 17, 19 and Comparative Examples 5 and 8. The results are shown below.
[0192] Example 2: Li / P=3.95, S / P=3.96, Br / P=0, I / P=1.03
[0193] Example 17: Li / P=3.95, S / P=3.95, Br / P=0.53, I / P=0.52
[0194] Example 19: Li / P=3.95, S / P=3.95, Br / P=1.04, I / P=0
[0195] Comparative Example 5: Li / P=3.55, S / P=4.01, Br / P=0.27, I / P=0.27
[0196] Comparative Example 8: Li / P=3.94, S / P=3.95, Br / P=0, I / P=1.03
[0197] [Table 1]
[0198]
[0199] Figure 2 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 1 to 4 are shown. Figure 3 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 5 to 8 are shown. Figure 4 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 9 to 12 are shown. Figure 5X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 13 to 16 are shown. Figure 6 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Examples 17 to 21 are shown. Figure 7 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Comparative Examples 1 to 5 are shown. Figure 8 X-ray diffraction patterns of the glass ceramic solid electrolytes prepared in Comparative Examples 6 to 11 are shown.
[0200] In the X-ray diffraction pattern obtained by the embodiment, a low-crystalline XRD spectrum can be obtained, thereby maintaining high ionic conductivity from the viewpoint of preventing the destruction of crystallites during compression of the glass-ceramic solid electrolyte, and maintaining a high filling rate from the viewpoint of preventing large voids between crystallites. In addition, since a low-crystalline XRD spectrum can be obtained for lithium halide, it can be considered that there will be no effect of solidifying the glass-ceramic solid electrolyte.
[0201] Industrial Applicability
[0202] The glass ceramic solid electrolyte of the present invention is preferably used as a constituent material of a lithium ion battery. In addition, the lithium ion battery of the present invention can be preferably used, for example, in batteries used in information-related equipment such as personal computers, video cameras and mobile phones, or in communication equipment, electric vehicles and other vehicles.
[0203] Several embodiments and / or examples of the present invention have been described in detail above, but it is easy for those skilled in the art to add more changes to these illustrative embodiments and / or examples without substantially departing from the novel teachings and effects of the present invention. Therefore, these more changes are also included in the scope of the present invention.
[0204] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are hereby cited.
Claims
1. A glass ceramic solid electrolyte, characterized in that: Containing lithium, phosphorus, sulfur and halogen as constituent elements, The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is 2.0 to 5.3, The molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is 2.0 to 4.5, The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.1 to 2.3, In powder X-ray diffraction using CuKα radiation, a peak A is present at a position of 2θ=20±1°, and in the powder X-ray diffraction, a peak B is not present at a position of 2θ=23.6±1°, or when the peak B is present, the peak intensity (I B ) and the peak intensity of peak A (I A ) peak intensity ratio (I B / I A ) is less than 0.050, The crystallite size of the glass ceramic solid electrolyte is 5 to 20 nm.
2. The glass ceramic solid electrolyte according to claim 1, characterized in that Peak intensity ratio (I B / I A ) is 0.
3. The glass ceramic solid electrolyte according to claim 1 or 2, characterized in that: Powder X-ray diffraction using CuKα rays showed a peak derived from lithium halide.
4. The glass ceramic solid electrolyte according to claim 3, characterized in that The crystallite size of the lithium halide calculated from the peak with the highest intensity among the peaks derived from the lithium halide is 5 to 100 nm.
5. The glass ceramic solid electrolyte according to any one of claims 1 to 4, characterized in that: The relative density of the 400MPa powder compact is above 90%.
6. The glass ceramic solid electrolyte according to any one of claims 1 to 5, characterized in that True density is 2.0~3.0g / cm 3 .
7. The glass ceramic solid electrolyte according to any one of claims 1 to 6, characterized in that The molar ratio (X / P) is greater than 0.
86.
8. The glass ceramic solid electrolyte according to any one of claims 1 to 7, characterized in that Two or more of the above halogens are contained.
9. The glass ceramic solid electrolyte according to claim 8, characterized in that The halogen includes iodine and bromine.
10. The glass ceramic solid electrolyte according to claim 9, characterized in that The molar ratio (I / P) of the iodine (I) to the phosphorus (P) is 0.0<(I / P)<1.8, The molar ratio (Br / P) of the bromine (Br) to the phosphorus (P) is 0.0<(Br / P)<1.
5.
11. The glass ceramic solid electrolyte according to any one of claims 1 to 10, characterized in that: The ionic conductivity is above 1 mS / cm.
12. A lithium ion battery, characterized in that: It comprises the glass ceramic solid electrolyte according to any one of claims 1 to 11.
Citation Information
Patent Citations
Production of lithium sulfide
JP1995330312A
Lithium ion conductive solid electrolyte and its manufacture
JP1997283156A
Method for producing lithium sulfide
JP2010163356A
Lithium sulfide and method for producing the same
JP2011084438A
Lithium, phosphorus, sulfur, and iodine-containing electrolyte and catholyte compositions, electrolyte membranes for electrochemical devices, and annealing methods for producing these electrolytes and catholytes
JP2019506699A